Pengembangan Sentra Industri Tas Dan Koper Tanggulangin Dalam Menghadapi MEA - Gusti Adriansyah; M. Adhi Prasnowo; A. Fathoni Rodli; Khoirul Hidayat (IAI Darussalam, 2017)
Small and Medium Enterprises (SMEs) play an important role and strategic for the country's economic growth in both developing and developed countries. At the time of the economic crisis in Indonesia, Small and Medium Enterprises is an economic sector that has the most excellent durability. The ability of SMEs needs to be empowered and developed constantly to try to reduce obstacles experienced by SMEs, so as to provide maximum contribution to improving the welfare of society. Tanggulangin industry is one of the SMEs which stood since 1939 when a few craftsmen begin manufacture of luggage bags and suitcases. And in 1976 founded Bags and Luggage Industry Cooperative (INTAKO), which initially had only 27 people.Venture capital obtained from the principal member. In a way, the cooperative continues to grow and the number of members has reached 354 artisans SMEs with assets of approximately US 10 billion. Tanggulangin product brand and has had a pretty good quality which has been recognized by consumers. But after the Lapindo mudflow, nearly 70 percent of artisans in Tanggulangin already folded. Some of them are surviving to working order. In addition invasion goods Chinese products very competitive price, but the quality is poor who also took part in the downturn. Practically, bags and suitcases industrial centers deserted visitors. Penelitian Tanggulangin This shows that the cause of the decline in sales is a flood of Chinese products, rising raw material prices, and the lack of innovation in product design. Therefore there is the need for guidance from the government in developing innovation in product design and innovation in marketing. Hence the existence of industrial centers Tanggulangin bags and suitcases can grow and create jobs for local residents as well as increasing revenue Sidoarjo